The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1142/s0219887821500262
|View full text |Cite
|
Sign up to set email alerts
|

A higher dimensional cosmological model for the search of dark energy source

Abstract: With due consideration of reasonable cosmological assumptions within the limit of the present cosmological scenario, we have analysed a spherically symmetric metric in 5D setting within the framework of Lyra manifold. The model universe is predicted to be a DE model, dominated by vacuum energy. The model represents an oscillating model, each cycle evolving with a big bang and ending at a big crunch, undergoing a series of bounces. The universe is isotropic and undergoes super-exponential expansion. The value o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 100 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…Recently, in [7], the authors study a higher dimensional cosmological model to find the origin of DE. They further predict an f (R, T) gravity model as a DE source [8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in [7], the authors study a higher dimensional cosmological model to find the origin of DE. They further predict an f (R, T) gravity model as a DE source [8].…”
Section: Introductionmentioning
confidence: 99%
“…This evidence had attracted several authors (Venkateswarlu and Kumar [26], Khadekar and Avachar [27], Bahrehbakhsh et al [28], Biswal et al [29], Venkateswarlu et al [30] Oli [31], Ramprasad et al [32], Rao et at. [33], Aygun et al [34], Caglar et al [35], Caglar and Aygun [36], Singh and Singh [37]) to study to the field of higher dimensions. We know that at beginning period of times before the universe has undergone compactification transitions the results of the field equations in general relativity and in scalar-tensor theories in higher dimensional space-time are of substantial purpose probably.…”
Section: Introductionmentioning
confidence: 99%
“…An LRS Bianchi type-I model in cosmology with bulk viscous fluid in Lyra geometry with the help of displacement vector depending upon time was constructed in (26) and found that the bulk viscosity decreases with time. In (27) a perfect fluid cosmological model in Lyra Geometry was studied by using constant deceleration parameter in five dimensional LRS Bianchi type-I Space-time.Considering reasonable cosmological assumptions within the limit of the present cosmological scenario, a spherically symmetric metric in five dimensional setting in the framework of Lyra geometry is analysed (28) . A cosmological model in 5D spherically symmetric space-time with energy momentum tensors of minimally interacting fields of dark matter and holographic dark energy in Brans-Dicke theory was constructed by (29) .…”
Section: Introductionmentioning
confidence: 99%